The effect of shoulder injury prevention program on shoulder isokinetic strength in young male volleyball players - Eshghi, S.; Zarei, M.; Abbasi, H.; Alizadeh, S. (Research in Sports Medicine, 2022)
The purpose of this study was to examine the effects of an eight-week 11+S programme on isokinetic shoulder strength in young male volleyball players. Twenty-eight top-level young male volleyball players were recruited for this study. The players were randomly assigned into intervention (14 players) and control (14 players) groups. The intervention group performed the 11+S as a warm-up before training at least three times a week for eight weeks. Dominant shoulder strength was measured using an isokinetic dynamometer at 60°/s and 180°/s. The functional deceleration ratio (FDR) was calculated as a functional strength profile. 20% FDR improvement after eight weeks of 11+S at 180°/s (p =0.003) were observed. No other statistically significant effects for shoulder strength improvement was observed (p >0.05). Eight weeks of 11+S warm-up programme improved the glenohumeral muscle imbalance by increasing the functional deceleration ratio (FDR) of shoulder muscles in young male volleyball players.